Kepercayaan Orang Bali terhadap Leyak sebagai Penyebab Penyakit dan Penanggulangannya - Nengah Bawa Atmadja (Antropologi Indonesia, 1997)
The Balinese believe that Leyak or ghost is an etiology of illness. To become a Leyak or to ngleyak, one must perform black magic or pangleyakan. The method of obtaining the pangleyakan is by studying under a dukun pangleyakan or dukun pangiwa, a special indigenous medical practitioner who masters the pangleyakan. A person can also obtain the pangleyakan from his/her parent. Moreover, he or she can request the pangleyakan to Goddess Durga, the goddess of black magic. When pangleyakan is used by somebody, he/she becomes a Leyak, and will have the ability to take the shape of a certain animal, a ghostly light, a body without a head - the varieties are endless. This can only be performed at night. A Leyak disturbs other people until they are sick or even die. Nevertheless, they believe that they can cope with the Leyak through the use of amulet or by performing the magical religious ritual.